STRENGTHENING CITIZHENSHIP DIGITAL EDUCATION IN SOCIAL MEDIA TO GROW GOOD DIGITAL CITIZEN IN FKIP STUDENTS, SYIAH KUALA UNIVERSITY - Ruslan, Ruslan; Haikal, Muhammad (Jurnal Ilmiah Teunuleh, 2022)
As for the Purpose   study   this   is   for describe Strengthening Citizhenship's Digital Education in Media Social for Grow Good Digital Citizen for FKIP Students at Syiah Kuala University, one of them for increase contribution results research for researchers and students for develop its potential Becomes media citizen _ social for grow good digital citizen for students of FKIP Syiah Kuala University (USK). Study qualitative is research used _ for research on conditions object natural with researcher as a key instrument. Analysis techniques in research this use method analysis information Miles as well as Huberman when information related strengthening Learning Digital Citizenship already collected, technique the validity of the data used in determine accuracy and credibility findings use triangulation source as well as member checking. Research results this is the first that is reinforcement education digital citizhensip in media social perception media safe social _ with indicators (Resiliense), Responsibility, (Reasoning), (Rights), both importance equip self with Skills think critical moment active in cyberspace with method that is argumentation, logic thinking, Values and rights. Third, Good Digital Citizen and Ethics for FKIP students at Syiah Kuala University (USK) through Ethics, Limit time, wise. With thereby could concluded study this have and know as well as understand information diera current digital citizenship this.